Phosphorus removal adsorbent as well as preparation method and application thereof
By mixing lightly flammed magnesium oxide powder with magnesium chloride solution and adding hydrogen peroxide solution, a lightweight porous phosphorus removal adsorbent was prepared, which solved the high cost and low efficiency problems of the existing phosphorus removal methods and achieved efficient and environmentally friendly phosphorus removal effect.
Patent Information
- Application Number
- CN202410177762.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-08
- Publication Date
- 2025-03-21
AI Technical Summary
Existing phosphorus removal methods such as chemical and biological methods have problems such as high chemical consumption, high cost and large mud production, or large area, high investment and poor stability. Traditional adsorption methods have problems such as selectivity, single efficacy and high cost, making it difficult to effectively deal with eutrophication of lakes and rivers.
A lightly calcined magnesium oxide powder is mixed with magnesium chloride solution, hydrogen peroxide solution is added, and after curing and natural curing, a lightweight porous phosphorus removal adsorbent is prepared, which has good phosphorus removal performance.
This phosphorus removal adsorbent has high efficiency phosphorus removal capability, low cost, simple preparation process, and does not release toxic ions. It is suitable for treating phosphorus-containing wastewater of various concentrations, and has good mechanical properties, making it easy to use on a large scale.
Smart Images

Figure CN119657063A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of adsorbent materials, and relates to a dephosphorization adsorbent and a preparation method and application thereof. The adsorbent has the function of dephosphorization and can be used in the fields of eutrophication control of lakes and rivers, dephosphorization treatment of sewage, etc. Background Art
[0002] With the development of the economy and the continuous changes and adjustments in the industrial structure, such as the continuous entry of metal surface treatment industries such as automobile manufacturing and communication facilities manufacturing, the phosphating process of metal surfaces has been widely adopted. The discharge of a large amount of high-concentration phosphorus-containing wastewater has led to serious eutrophication of water bodies, causing large-scale red tides and algal blooms. It is particularly important to strengthen the treatment of phosphorus in sewage and strictly control the phosphorus content in the discharged water. At present, the commonly used phosphorus removal methods are mainly chemical and biological methods. The chemical method consumes a large amount of reagents, is expensive, and produces a large amount of sludge, while biological phosphorus removal occupies a large area, has high investment, and has poor stability. Both have shortcomings. Therefore, it is necessary to find an efficient treatment method.
[0003] Adsorption is a method with obvious advantages in treating wastewater, and has become the focus of water treatment research. At present, many adsorbents with good performance have been developed at home and abroad, especially the use of industrial waste and crop residues as adsorbents, and the modification of existing adsorbents to improve their adsorption performance has become a hot topic in recent years. For example, zeolite, medical stone, bituminous coal ash, slag, modified rice husk, chitosan, etc. Traditional adsorption methods, whether physical adsorption or chemical adsorption, generally have the following problems: selectivity, single effect and high cost. Especially for the restoration of large areas of water such as lake and river restoration, there is currently no adsorbent with long-lasting effect and low cost that can be applied. Therefore, it is very meaningful to study low-cost and high-efficiency phosphorus removal methods to improve natural and economic benefits.
[0004] Magnesium cement is a special type of cement. Because it was invented by the Frenchman Sorel in 1867, it is also called magnesium oxychloride cement. Magnesium cement is a cementitious material formed by using light-burned powder obtained by calcining magnesite ore or ash powder obtained by low-temperature calcining dolomite (the main component is light-burned MgO) as a binder, magnesium chloride, magnesium sulfate or magnesium phosphate and other water-soluble salts as a blending agent, and adding water. It includes magnesium oxychloride cement, magnesium oxysulfate cement and magnesium phosphate cement. Among them, the hardened body formed by magnesium oxychloride cement is mainly composed of magnesium oxide-magnesium chloride-water ternary compound crystal phase complex salt composed of 5Mg(OH)2·MgCl2·8H2O and 3Mg(OH)2·MgCl2·8H2O crystal phases, and there is also a part of Mg(OH)2 gel.
[0005] In the field of adsorbents, magnesium-containing phosphorus removal agents also have certain applications. They mainly include MgCl2-modified attapulgite, MgAl layered metal-modified biochar, MgO-modified biochar, and magnesium alginate-modified biochar microspheres, which are usually made by mixing nano-magnesium oxide, magnesium chloride or magnesium sulfate, using other adhesives to form, and undergoing complex cleaning, roasting and other processes. The above-mentioned adsorbents have the disadvantages of complex preparation, high cost, and difficulty in resource recovery, so they have not yet been widely used.
[0006] Magnesium cement has been widely used in the fields of construction, decoration, production of packaging materials, transportation facilities, production of handicrafts, etc. However, there is no report on its application in phosphorus removal agent. Summary of the invention
[0007] The purpose of the present invention is to provide an adsorbent which can treat phosphorus-containing sewage and wastewater of various concentrations, has a simple preparation process, low cost and no secondary pollution, and a preparation method and application thereof.
[0008] To achieve the above object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a dephosphorization adsorbent, comprising:
[0010] (1) Preparation of adsorbent slurry: First, light-burned magnesium oxide powder is added to a magnesium chloride solution and stirred to obtain a first slurry; then, a hydrogen peroxide solution is added to the first slurry and stirred to obtain a second slurry;
[0011] (2) Molding: pouring the second slurry into a mold, demolding after solidification, and then naturally curing to obtain a lightweight porous adsorbent block.
[0012] The above-mentioned method for preparing the phosphorus removal agent, as a preferred embodiment, further comprises the step of: (3) crushing and sieving the lightweight porous adsorbent block obtained in step (2) to obtain a granular adsorbent with a desired particle size.
[0013] As a preferred embodiment of the preparation method of the above-mentioned dephosphorization adsorbent, in step (1), the activity of the light-burned magnesium oxide powder is 40-70%, that is, the active magnesium oxide in the light-burned magnesium oxide accounts for 40-70%.
[0014] As a preferred embodiment of the method for preparing the above-mentioned dephosphorization adsorbent, in step (1), the concentration of the magnesium chloride solution is 15-28%.
[0015] As a preferred embodiment of the preparation method of the above-mentioned phosphorus removal adsorbent, in step (1), the molar ratio of active magnesium oxide to magnesium chloride in the light-burned magnesium oxide is 7:1-10:1 (such as 7.5:1, 8:1, 8.5:1, 9:1, 9.5:1, etc.).
[0016] As a preferred embodiment of the above-mentioned method for preparing the dephosphorization adsorbent, in step (1), the hydrogen peroxide solution is added in an amount of 1-1.5% of the first slurry at a concentration of 30%.
[0017] In the above-mentioned method for preparing the phosphorus removal agent, as a preferred embodiment, in step (2), the curing time is 6-10 hours; preferably, the natural curing time is 2-3 days.
[0018] In a second aspect, the present invention provides a phosphorus removal adsorbent prepared by the above method.
[0019] Preferably, when the phosphorus removal adsorbent is a granular adsorbent, the particle size is 0.10-2 mm (such as 0.15 mm, 0.3 mm, 0.5 mm, 0.8 mm, 1.0 mm, 1.2 mm, 1.5 mm, 1.8 mm, etc.)
[0020] In a third aspect, the present invention provides an application of a dephosphorization adsorbent, and the dephosphorization adsorbent is used to treat phosphorus-containing wastewater.
[0021] In the application of the above-mentioned phosphorus removal adsorbent, as a preferred embodiment, the speculative dosage of the phosphorus removal adsorbent is 2g / L-5g / L (such as 2.5g / L, 3.0g / L, 3.5g / L, 4.0g / L, 4.5g / L, etc.).
[0022] In the application of the above-mentioned phosphorus removal adsorbent, as a preferred embodiment, the treatment temperature is 298K-318K (such as 300K, 302K, 305K, 308K, 310K, 312K, 315K, etc.), and the treatment time is 6h-12h.
[0023] In the application of the above-mentioned dephosphorization adsorbent, as a preferred embodiment, the treatment temperature is 303K-318K, and the treatment time is 3h-12h.
[0024] Compared with the prior art, the solution of the present invention has the following beneficial effects:
[0025] (1) The phosphorus removal adsorbent of the present invention has the advantages of strong adsorption capacity, wide source, and low cost, which are superior to most other adsorbents;
[0026] (2) The phosphorus removal adsorbent of the present invention can be a porous block, which has the characteristics of light weight and high strength of ceramsite and volcanic rock, and is easier to separate after use than powdered adsorbents;
[0027] (3) The phosphorus removal adsorbent of the present invention is a fluid before molding and can be made into various sizes and shapes such as particles, blocks, walls, etc., and has good mechanical properties (average compressive strength is 7 MPa). Compared with other adsorbent materials, it is conducive to large-scale application.
[0028] (4) The phosphorus removal adsorbent of the present invention is environmentally friendly and will not release toxic ions into water. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The results of the batch adsorption experiment in Example 1 are shown; wherein (a) shows the effect of MCM dosage on PO4 adsorption; (b) shows the effect of adsorbent particle size on PO4 adsorption; (c) shows the effect of initial pH on PO4 adsorption; and (d) shows the effect of coexisting ions on PO4 adsorption. The experimental conditions are as follows: initial concentration: 100 mg P / L; temperature: 298K; contact time: 24 hours; rotation speed: 200 rpm.
[0030] Figure 2 The kinetic experimental results of phosphate adsorption on MCM in Example 1 are shown; wherein (a) shows the data simulation of pseudo-first order and pseudo-second order; (b) shows the Weber-Morris model; (c) shows the equilibrium isotherm of phosphate adsorption on MCM. The experimental conditions are as follows: initial concentration: 100 mg P / L; pH value: 7.0; temperature: 298-318K; MCM dosage: 5 g / L; rotation speed: 200 rpm; contact time: 24 hours.
[0031] Figure 3 Figure (a) shows the changes in adsorbed phosphate, solution pH and Mg ion concentration during the adsorption process in Example 1; (b) is an XRD graph; (c) is an enlarged view of Figure (b); (d) is an FTIR graph of MCM and MCM after adsorption (different adsorption retention times: 0h, 0.5h, 3h, 10h, 12h and 24h); Figure 3 Figures (e) and (f) are the core energy level spectra of Mg 2p (e) and P 2p (f) of P adsorbed MCM, respectively. The experimental conditions are as follows: initial concentration: 100 mg P / L; pH value 7.0; temperature: 298K; MCM dosage: 5 g / L; rotation speed: 200 rpm; contact time: 24 hours.
[0032] Figure 4 shows the SEM photos of MCM and MCM after adsorption in Example 1, where (a) is the SEM photo of MCM before adsorption, and (b) to (e) are SEM photos of different adsorption times (specifically 0.5h, 2h, 3h and 6h). Figures (g) to (k) show EDS photos of MCM and MCM after adsorption at 0h, 0.5h, 2h, 3h and 6h (g~k). Figures (f) and (l) are the SEM photo and EDS analysis of the internal structure of MCM after 2h of adsorption, respectively. The experimental conditions are as follows: initial concentration: 100mg P / L; pH value 7.0; temperature: 298K; MCM dosage: 5g / L; rotation speed: 200 rpm; contact time: 24 hours.
[0033] Figure 5 (a) shows HPO4 2- Optimized geometric structure of the adsorption configuration on the OH site of Mg(OH)2 (a) (side view), (b) shows the optimized geometric structure of the adsorption configuration on the OH site of Mg3(OH)5Cl·4H2O (side view), (c) shows the optimized geometric structure of the adsorption configuration on the H2O site of Mg3(OH)5Cl·4H2O (side view).
[0034] Figure 6 The results of the determination of the zero charge point of MCM of Example 1 are shown. The experimental conditions are as follows: ionic strength, 0.01 mol / L NaCl; temperature T, 298K.
[0035] Figure 7 The nitrogen adsorption / desorption isotherm curve and pore size distribution of MCM before adsorption in Example 1 (inset);
[0036] Figure 8 The nitrogen adsorption / desorption isotherm curve and pore size distribution of MCM after adsorption in Example 1 (inset). DETAILED DESCRIPTION
[0037] The present invention will be further described in detail below through examples. The protection scope of the present invention includes but is not limited to the following examples.
[0038] If no specific experimental steps or conditions are specified in the examples, the experiments can be carried out according to the conventional steps or conditions described in the literature in the art.
[0039] Unless otherwise specified, all reagents and raw materials used in the examples are commercially available products.
[0040] Example 1
[0041] 1. Raw material preparation
[0042] Analytical grade MgCl2·6H2O, NaOH, and KH2PO4 were purchased from China National Pharmaceutical Group Chemical Reagent Co., Ltd., and light-burned MgO was purchased from Haicheng Huafeng Mining Co., Ltd., Liaoning Province, China. The stock phosphate solution was prepared by dissolving KH2PO4. PO4 was diluted with dilute HCl or NaOH. 3- The pH of the working solution was readjusted to 7.0.
[0043] 2. Preparation of magnesium-based cement-based adsorbent material (MCM)
[0044] MCM was synthesized by mixing 100 g of light-burned MgO with 80 g of 25% MgCl2 solution for 2 minutes. Subsequently, 2 g of 30% hydrogen peroxide solution was added to the mixture and stirred for another minute until a uniform mixture was obtained. The resulting slurry was transferred to a prismatic mold and cured under natural conditions for 6 h (hours) before demoulding. The demoulded material was stored in a natural environment for 3 d (days) to obtain a lightweight porous adsorbent block. The obtained block was crushed and sieved to obtain granular adsorbents of various particle size ranges.
[0045] 3. Phosphate adsorption experiment
[0046] (1) Effect of different MCM dosages on adsorption. 0.60 g, 0.30 g, 0.15 g, 0.10 g, 0.06 g and 0.03 g of adsorbent (MCM, particle size 20-40 mesh, i.e. 0.38-0.83 mm) and 30 mL of 100 mg / L standard KH2PO4 solution were added to a 100 mL glass flask with an initial pH of 7.0. The sample was shaken at 298 K for 24 h and then filtered with a 0.45 μm membrane.
[0047] (2) Effect of different MCM particle sizes on adsorption. 0.2 g of adsorbents with three different particle sizes (0.15-0.38 mm, 0.38-0.83 mm, and 0.83-1.7 mm) were placed in glass flasks, each containing 40 mL of 100 mg / L KH2PO4 solution (as P) at pH 7.0 and 298 K, and shaken continuously for 24 h to reach equilibrium.
[0048] (3) Effect of different initial solution pH values on phosphorus removal. The effect of initial solution pH values ranging from 4 to 10 on phosphate removal was evaluated by adding 0.15 g of the adsorbent (MCM) to 30 mL of 100 mg / L KH2PO4 solution (as P) in a 100 mL glass flask. Dilute NaOH and HCl were prepared for initial pH adjustment.
[0049] (4) Coexisting anion Na + , Cl - 、SO4 2-、HCO3 - and NO3 - The effect of coexisting anions Na on phosphate elimination was studied in batch experiments using 100 mg / L KH2PO4 solution (as P). + , Cl - 、SO4 2- 、HCO3 - and NO3 - Effect on phosphate elimination. The concentrations of coexisting anions were set at 1.0 and 10.0 mmol / L, respectively. The concentration of phosphate was measured according to the ammonium molybdate spectrophotometric method (Determination of total phosphorus in water quality - ammonium molybdate spectrophotometric method (GB 11893-89)).
[0050] (5) Solution of the adsorption kinetics of phosphate on MCM. In order to gain a deeper understanding of the adsorption kinetics of phosphate on MCM, 1 g of MCM (100 mg / L, P) was added to 200 mL of phosphate solution. The initial pH was readjusted to around 7.0. Samples were taken from the suspension at pre-arranged time intervals (0.5 h, 1 h, 2 h, 3 h, 4 h, 6 h, 8 h, 10 h, 12 h, and 24 h) and then filtered. The experimental data were fitted using a pseudo-first-order equation (Equation 1) and a pseudo-second-order equation (Equation 2). The intraparticle diffusion model (Equation 3) was used to explore the diffusion process.
[0051]
[0052]
[0053] Q t =K id t 0.5 (3)
[0054] Phosphate adsorption isotherms were obtained for different phosphate concentrations (5-1000 mg / L) at temperatures of 298, 308, and 318 K. After 24 h of oscillation, the phosphate concentration was determined. Four models were used to analyze the experimental data, namely the Langmuir model (Equation 4), the Freundlich model (Equation 5), the Langmuir-Freundlich model (Equation 6), and the Redlich-Peterson model (Equation 7).
[0055] Q e =K L Q m C e / (1+K1C e ) (4)
[0056]
[0057]
[0058]
[0059] Where: K L (L / mg), K F (mg (1-1 / n) ·L (1 / n) ·g -1 ), K LF (L 1 / n mg -1 / n ) and K R (L / g) are Langmuir, Freundlich, Langmuir-Freundlich and Redlich-Peterson constants. Qm is the theoretical maximum adsorption capacity (mg / g), also known as the monolayer coverage of the surface, Ce (mg / L) is the equilibrium solution concentration of sorbate, 1 / n is the Freundlich linear constant, α R (L β mg -β ) is the Redlich-Peterson constant and β is a coefficient between 0 and 1.
[0060] 4. Analytical methods
[0061] The porosity of MCM was determined by using an automated adsorption device (Quantachrome Nova 4000e system). The specific surface area (S) was analyzed using the Brunauer-Emmett-Teller (BET) method and the Barrett-Joyner-Halenda (BJH) method. BET ) and pore size distribution. The surface morphology was obtained using a ZEISS Gemini 300 scanning electron microscope (SEM). The surface elements were analyzed using energy dispersive X-ray spectroscopy (EDX). The zero charge point (pH zpc According to GB / T17671-1999, the compressive strength of MCM was evaluated using a DYE-300 microcomputer-controlled electronic universal testing machine (Hebei Longchen Weiye Instrument Manufacturing Co., Ltd.).
[0062] The crystal structure of MCM was measured by using a Rigaku Ultima IV X-ray diffraction system equipped with Cu Kα radiation. The surface functional groups of MCM were characterized by Fourier transform infrared (FT-IR) spectroscopy (Mattson 5000 FTIR spectrometer). -13The chemical composition of phosphate adsorbed on MCM was measured using X-ray photoelectron spectroscopy (XPS, Thermo Scientific ESCALAB Xi+) equipped with Al Kα radiation (1488.6 eV) under Pa vacuum at a power of 150 W. Data processing was done by using XPSpeak 41 software.
[0063] 5. Results and Discussion
[0064] 5.1 Batch adsorption experiments
[0065] 5.1.1 Effect of MCM dosage and particle size
[0066] The amount of adsorbent used is a key factor in evaluating the efficacy and potential of the adsorbent. Figure 1 a shows that the phosphate removal rate is improved with the increase of MCM content. When 2g / L MCM is used, the phosphate removal rate is 87.6%. When the content is 5g / L MCM, the phosphate removal rate reaches 94.6% and the TP residual is 5.4mg / L. Further increase in the amount of MCM has little effect on phosphorus removal. Based on this result, 5g / L MCM was selected for further study. Compared with other dephosphorization materials such as sand, attapulgite, fly ash / water plant sludge / oyster shell ceramsite, the amount of MCM required for phosphorus adsorption is much lower (see Table 1 below for details).
[0067] Effect of adsorbent particle size on phosphorus removal performance Figure 1 As shown in b. With the increase of adsorbent particle size, PO4 3- No substantial change was observed in the removal efficiency. The equilibrium adsorption capacity of phosphorus for the three MCMs with different particle sizes was about 20 mg / g. The final pH value of the solution reached 10. This may indicate that physical adsorption is not the main adsorption mechanism for the MCM adsorbent, and precipitation may be involved when the pH value of the mixed solution changes from 7 to 10, which favors the formation of precipitates, that is, Ca-P precipitation on the slag surface is the main mechanism of phosphate removal.
[0068] 5.1.2 Effects of pH and coexisting ions
[0069] like Figure 1As shown in Figure c, the adsorption of phosphate on MCM did not change much within the pH range tested. The adsorption amount reached 19.84 mg / g when the initial pH was 4.0. Further increase in the initial pH had little effect on the adsorption capacity. This result indicates that the adsorption of phosphate on MCM is not hindered by the initial pH of the solution and shows good adaptability. Since the solution pH is far below the zero charge point of MCM, MCM is expected to be positively charged, thus facilitating phosphate adsorption. However, the competitive adsorption effect of hydroxyl ions is relatively small, indicating that electrostatic interaction is not the main adsorption mechanism. The effect of coexisting ions on the adsorption of phosphate by MCM is shown in Figure 2. Figure 1 d. The experimental results show that Na + , Cl - 、NO3 - 、CO3 2- and SO4 2- The effect on the amount of phosphate adsorption was negligible. Although the anion content increased 10 times, the adsorption efficiency of PO4 ions was still able to reach more than 95%, indicating that the coexisting ions had little effect on phosphorus removal by MCM. These results indicate that MCM has a high adsorption selectivity for PO4 anions and has great potential to eliminate PO4 from surface water. This finding once again shows that physical adsorption is not the main adsorption mechanism and that phosphorus removal involves multiple adsorption mechanisms.
[0070] 5.1.3 Adsorption kinetics
[0071] Kinetic experiments were performed to determine the reaction time required to achieve equilibrium of phosphate adsorption on MCM. Figure 2 As shown in a, at a temperature of 298K, the phosphate adsorbed on MCM increased rapidly within the first 4 hours and then slowed down in the later stage of the experiment. After 6 hours of adsorption, about 84% of the phosphate was adsorbed. Further increase in adsorption time (>6h) resulted in a slower adsorption rate until equilibrium was reached. At higher temperatures of 308K and 318K, the adsorption process accelerated. Based on the kinetic results, 24h was selected for the equilibrium experiment. The adsorption kinetic data were simulated using pseudo-first-order and pseudo-second-order models. The results show that the pseudo-first-order model (R 2 =0.9672, 0.9833, 0.9647) are better than the pseudo second-order model (R 2 =0.9429, 0.9620, 0.9254).
[0072] In order to clarify the diffusion process of solute ions inside MCM, the Weber-Morris model was applied. Figure 2As shown in (b), at a temperature of 298K, the results show three different slopes, indicating that the adsorption of phosphate on MCM is a multi-step process. In the first stage, a small portion of phosphate is rapidly absorbed, probably due to film diffusion or boundary layer diffusion. The adsorption rate increases significantly in the next stage, indicating that there are a large number of binding sites and abundant phosphate ions in the solution. The adsorption of phosphate is much slower in the third stage, which may involve the migration of phosphate molecules from the surface to the internal micropores. This result indicates that intraparticle diffusion is the rate-limiting step. In general, since the adsorption rate is faster on the surface of larger pores and slower on the surface of micropores, it can be concluded that the fast adsorption on the outer surface and the slow diffusion within the particle simultaneously determine the adsorption process.
[0073] 5.1.4 Adsorption isotherms
[0074] The adsorption equilibrium isotherm of MCM is shown in Figure 2 c. As the temperature increases, the phosphate adsorption of MCM increases, reaching 42.0, 64.0 and 72.0 mg / g, respectively. 2 =0.7848), the Langmuir model (R2 = 0.9531), the Langmuir-Freundlich model (R 2 =0.9537) and the Redlich-Peterson model (R 2 =0.9513) provides a better fit to the experimental data at 298 K. At 308 K and 318 K, the Redlich-Peterson model (R 2 =0.9796,0.9541) than the Langmuir model (R 2 =0.9514,0.9151), Langmuir-Freundlich model (R 2 =0.9677,0.9173) and the Freundlich model (R 2 =0.9243,0.9117) better reproduced the adsorption experimental data, indicating that the interaction between phosphate and MCM is affected by Langmuir and Freundlich processes. This also shows that the adsorption of phosphorus by MCM is a heterogeneous process affected by multiple factors. This finding is consistent with the conclusion of the kinetic study that multiple mechanisms simultaneously control the adsorption process.
[0075] 5.2 Adsorption mechanism
[0076] A comprehensive understanding of the adsorption mechanism of MCM is crucial for the evaluation and utilization of MCM. To clarify the adsorption mechanism of MCM, the adsorption process of MCM was systematically observed. The structural and morphological changes of MCM during the adsorption process were studied by XRD, FTIR, BET, SEM and EDS. The chemical state of phosphorus adsorbed on MCM was studied by XPS technology.
[0077] like Figure 3 As shown in Figure 1, the change in the solution pH exhibited three distinct stages. In the initial stage, the solution pH was found to increase rapidly upon adsorption of a small amount of phosphate. This behavior can be explained by the rapid protonation of the magnesium-supported phase, including Mg(OH)2 and Mg3(OH)5Cl·4H2O, which reduces the content of hydrogen ions and thus increases the solution pH because the solution pH is well below the zero charge point of MCM ( Figure 6 ). At the same time, the positively charged surface groups on the outer surface of MCM attract HPO4 through electrostatic attraction. 2- reaction occurs. A rapid increase in Mg ion concentration was also observed, which can be attributed to the dissolution of the Mg3(OH)5Cl·4H2O phase on the outer surface of the MCM. The second stage is a rapid adsorption stage, characterized by a relatively stable pH value (between 8.5 and 9) and a decrease in Mg ions, which is consistent with the kinetic results. The adsorption capacity can also be determined by this stage. The third stage is the final equilibrium stage, characterized by a further increase in pH, which can be explained by the transformation of Mg3(OH)5Cl·4H2O to Mg(OH)2, which is affected by the transport process from micropores to macropores.
[0078] To gain a deeper understanding of the mechanism, the adsorption-induced phase transition of MCM was analyzed. Figure 3 As shown in Figure b, at 2θ values of 18.8° and 38.2°, the intensity of the crystalline Mg(OH)2 peak gradually increased, while the crystallinity of Mg3(OH)5Cl·4H2O decreased, indicating the transformation of Mg3(OH)5Cl·4H2O to Mg(OH)2. At the same time, two new peaks corresponding to MgHPO4 were found at 2θ values of 28.6° and 29.48° after 0.5 h, verifying the presence of magnesium hydrogen phosphate. Fourier transform infrared spectroscopy also confirmed this change. Before adsorption, about 1014 cm -1 The peak at 2- , and its intensity increases after adsorption. This peak is at about 1014cm -1 The increase in intensity at 2- In addition, 869cm -1The peak at can be attributed to the PO-Mg complex with A1 symmetry, indicating the formation of an inner sphere surface complex (MOP) between phosphate and MCM. Due to the abundance of hydroxyl functional groups, the phosphate adsorption mechanism may also occur through ligand exchange between hydroxyl groups on the MCM surface and phosphate ions.
[0079] The present application also studied the morphological changes during the MCM adsorption process. As shown in Figure 4, phosphorus was evenly distributed on the MCM at the initial 0.5 h, and no obvious crystals were found. After 2 h of adsorption, nanoscale Mg-P clusters were clearly observed on the needle-like crystals, which can be attributed to the crystallization of Mg-P salt particles. The element distribution diagram is Figure 4g-l The nanoscales have a higher phosphorus content, indicating that the crystallization of Mg-P salt particles prefers to nucleate and grow on needle-shaped crystals. As shown in Figure 4d, at 3 h, large plate-like clusters mainly composed of Mg, O and P precipitates were found on the outer surface of MCM, and the accumulation of the outer precipitation layer was obvious over time (Figures 4d and 4e). The accumulation of Mg-P precipitates is consistent with Figure 3 The second adsorption stage shown in a, which is characterized by the reduction of Mg ions, indicates that the precipitation process affected by the released Mg ions may be the main mechanism of P adsorption.
[0080] To verify the immobilization of phosphorus on MCM, the P 2p and Mg 1S spectra of MCM after adsorption were analyzed. Figure 3 e shows the high-resolution P 2p spectrum, which is resolved into two peaks at 133.0 and 133.7 eV, corresponding to POM and HPO4, respectively. 2- . Figure 3 The Mg 2p spectrum in f shows peaks at 50.4 and 49.7 eV, attributed to MgO and Mg(OH)2, respectively, and a peak at 51.5 eV, corresponding to MgHPO4. XPS analysis confirmed the immobilization of phosphorus on MCM and further confirmed the inner-sphere complexation reaction during adsorption via a ligand exchange process.
[0081] Nitrogen adsorption isotherms before and after MCM adsorption Figure 7 and Figure 8 The nitrogen adsorption isotherm of MCM can be classified as type IV with an H3 hysteresis loop, which means the presence of narrow slit-like pores. Figure 7 As shown in (inset), the pore size distribution curve is broad and multi-peaked, and small mesopores (about 2-5 nm) and larger mesopores (about 30-80 nm) can be observed, which indicates that the adsorption of phosphorus on MCM may not be a simple process. 2 / g increased to 14.006m 2 / g, and the average pore size expanded from 3.403 nm to 11.474 nm, which can be attributed to the dissolution of Mg3(OH)5Cl·4H2O and the precipitation, nucleation and crystallization of cluster crystals on MCM.
[0082] In summary, the removal of phosphorus by MCM is not a simple adsorption process. Kinetic simulations, adsorption isotherms, changes in pH and magnesium concentration in solution, and changes in the structure and morphology of MCM indicate that the adsorption of phosphate is controlled by multiple mechanisms. The entire removal process can be speculated to involve electrostatic attraction, intrasphere complexation, ligand exchange, crystal nucleation and crystallization, and precipitation. This reasonably explains why the effects of pH and coexisting ions on the adsorption efficiency are negligible.
[0083] 5.3 Comparison with other adsorbents for PO4 removal
[0084] An increasing number of adsorbents have been evaluated for the elimination of PO4 from environmental water. However, due to the lack of standardized batch adsorption experimental procedures, it is difficult to directly compare different materials due to the variation in experimental conditions. To illustrate the potential applicability of the proposed MCM for phosphate removal from water, the adsorption capacity and experimental parameters of different phosphate adsorbents are comparatively evaluated in Table 1. Under similar conditions, the MCM showed higher PO4 adsorption capacity compared with sand, attapulgite, and lightweight aggregate. La / Fe co-modified attapulgite, MgAl LDH, and La-AmGO@AmCs microspheres showed higher capacity for PO4, but the preparation processes of these materials were complicated. The biochar / MgAl-LDH ultrafine composite had the greatest phosphate adsorption capacity, but the small particle size limited its application. The sustainable ceramsite matrix based on fly ash / water plant sludge / oyster shell had a larger particle size, but slightly lower adsorption capacity and mechanical properties (average compressive strength of 0.9 MPa). In this study, the proposed MCM demonstrated effective PO4 removal and outperformed most other adsorbents in the available data. Another advantage of the MCM of the present application is its cost-effectiveness and excellent mechanical properties (average compressive strength of 7Mpa), which is conducive to large-scale application compared with other adsorbent materials. In addition, the MCM of the present application is environmentally friendly and does not release toxic ions into the water.
[0085] Table 1 Summary of parameters of different adsorbents
[0086]
[0087] In Table 1, the evaluation of sand as an adsorbent can be found in the literature (BK Mayer, LABAker, TH Boyer, P. Drechsel, M. Gifford, MA Hanjra, P. Parameswaran, J. Stoltzfus, P. Westerhoff, BERittmann, Total value of phosphorus recovery, Environ. Sci. Technol. 50 (2016) 6606-6620.); the evaluation of attapulgite as an adsorbent can be found in the literature (F. Gan, J. Zhou, H. Wang, C. Du, X. Chen, Removal of phosphate from aqueous solution by thermally treated natural palygorskite, Water Res. 43 (2009) 2907-2915.); the evaluation of lightweight aggregate as an adsorbent can be found in the literature (T. Zhu, PD Jenssen, T. Maehlum, T. Krogstad, Phosphorus sorption and chemical characteristics of lightweight aggregates (LWA) - Potential filter media in treatment wetlands, Water Sci. Technol. 35 (1997) 103-108.); for the evaluation of lanthanum / iron co-modified attapulgite as an adsorbent, see the literature (S. Liu, S. Zhao, F. Fan, B.-T. Zhang, S. Wang, Magnetically separable and recyclable lanthanum / iron co-modified attapulgite: A sustainable option to efficiently control phosphate loading, Journal of Cleaner Production 348 (2022) 131294.); for the evaluation of La-AmGO@AmCs microspheres as adsorbents, see the literature (ASEltaweil, K. Ibrahim, EMAbd El-Monaem, GMEl-Subruiti, AMOmer, Phosphate removal by Lanthanum-doped aminated graphene oxide @ aminated chitosan microspheres: Insights into the adsorption mechanism, Journal of Cleaner Production 385 (2023) 135640.); For the evaluation of MgAl LDH as an adsorbent, see the literature (K. Kuzawa, YJ Jung, Y. Kiso, T. Yamada, M. Nagai, TGLee, Phosphate removal and recovery with a synthetic hydrotalcite as an adsorbent, Chemosphere 62 (2006) 45-52.); For the evaluation of biochar / MgAl-LDH ultrafine composites as adsorbents, see the literature (M. Zhang, B. Gao, Y. Yao, M. Inyang, Phosphate removal ability of biochar / MgAl-LDH ultra-fine composites prepared by liquid-phase deposition, Chemosphere 92 (2013) 1042-1047.); the evaluation of sustainable ceramsite substrate from coal fly ash / waterworks sludge / oyster shell as adsorbent can be found in the literature (G. Cheng, Q. Li, Z. Su, S. Sheng, J. Fu, Preparation, optimization, and application of sustainable ceramsite substrate from coal fly ash / waterworks sludge / oyster shell for phosphorus immobilization in constructed wetlands, Journal of Cleaner Production 175 (2018) 572-581.). .
[0088] In summary, this application illustrates the excellent performance of MCM in phosphate immobilization and recovery. MCM exhibits significant phosphate adsorption capacity, and parameters such as initial pH and coexisting ions have negligible effects on phosphate removal. The interaction mechanism may involve electrostatic attraction, inner sphere complexation, ligand exchange, crystal nucleation and crystallization, and precipitation. The magnesium hydrogen phosphate precipitate obtained after adsorption can be used as a phosphate fertilizer and magnesium fertilizer to recycle phosphate in surface water. MCM is a promising adsorbent for phosphate elimination and recovery due to its advantages such as available raw materials, simple production process, non-toxicity, high bioavailability, high cost-effectiveness, and good mechanical strength. Considering the abundance of magnesium and OH groups in MCM, MCM may also be helpful for long-term eradication of phosphate.
[0089] From a human perspective, there is an urgent need for efficient and environmentally friendly materials that can effectively capture phosphorus to complete the phosphorus cycle. The methods and results of this study can be used to synthesize and apply sustainable and environmentally friendly materials for phosphorus recovery, eutrophication reduction, soil fertilization, soil quality improvement, and carbon sequestration. The MCM provided in this application can obtain MgHPO4 precipitate after use, which can be used as a slow-release agricultural fertilizer, thereby enabling the recovery of phosphorus and magnesium for plant use. In addition, China has abundant magnesium ore resources, and a large amount of easily available and low-cost MgCl2·6H2O can be recovered from the by-products of the salt industry. The large-scale production and implementation of MCM are promising. In addition, MCM has great potential in surface runoff pollution control because it can be used to produce porous, lightweight materials such as paving materials, permeable bricks, and wetland filter materials, which can effectively capture phosphorus from surface runoff. Therefore, further research is needed to investigate the behavior of MCM in pilot and field demonstrations.
[0090] It should be noted that, in the present invention, unless otherwise understood in conjunction with the full text, the expression "A / B" should be interpreted as any one of the following three parallel situations: A; B; A and B.
[0091] It should also be noted that, in the present invention, in addition to being understood otherwise in conjunction with the full text, if any, the relevant terms should be understood as follows. Relational terms such as first and second, etc. are only used to distinguish an entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the term "includes", "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements that are not clearly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements limited by the sentence "comprising one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements.
[0092] Although the present invention has been disclosed above by the description of the specific embodiments of the present invention, it should be understood that those skilled in the art can design various modifications, improvements or equivalents of the present invention within the spirit and scope of the attached scheme. These modifications, improvements or equivalents should also be considered to be included in the scope of protection claimed by the present invention.
Claims
1. A method for preparing a dephosphorization adsorbent, characterized in that: The steps include: (1) Preparation of adsorbent slurry: First, light-burned magnesium oxide powder is added to a magnesium chloride solution and stirred to obtain a first slurry; then, a hydrogen peroxide solution is added to the first slurry and stirred to obtain a second slurry; (2) Molding: pouring the second slurry into a mold, demolding after solidification, and then naturally curing to obtain a lightweight porous adsorbent block.
2. The method for preparing a dephosphorization adsorbent according to claim 1, characterized in that: Also includes the steps: (3) Granulation: The lightweight porous adsorbent block obtained in step (2) is crushed and sieved to obtain a granular adsorbent with a desired particle size.
3. The method for preparing the dephosphorization adsorbent according to claim 1 or 2, characterized in that: In step (1), the molar ratio of active magnesium oxide to magnesium chloride in the light-burned magnesium oxide is 7:1-10:1; Preferably, the activity of the light-burned magnesium oxide powder is 40-70%; Preferably, the concentration of the magnesium chloride solution is 15-28%.
4. The method for preparing a dephosphorization adsorbent according to any one of claims 1 to 3, characterized in that: In step (1), the hydrogen peroxide solution is added in an amount of 1-1.5% of the first slurry at a concentration of 30%.
5. The method for preparing a dephosphorization adsorbent according to any one of claims 1 to 4, characterized in that: In step (2), the curing time is 6-10 hours; preferably, the natural curing time is 2-3 days.
6. A phosphorus removal adsorbent, characterized in that: The method is prepared by any one of claims 1 to 5.
7. The phosphorus removal adsorbent according to claim 6, characterized in that: When the dephosphorus adsorbent is a granular adsorbent, the particle size is 0.10-2 mm.
8. An application of a dephosphorization adsorbent, characterized in that: The phosphorus-containing wastewater is treated by using the phosphorus removal adsorbent as described in claim 6 or 7.
9. The use of the dephosphorization adsorbent according to claim 8, characterized in that: The speculative dosage of the dephosphorization adsorbent is 2 g / L-5 g / L.
10. The use of the above-mentioned phosphorus removal adsorbent according to claim 8 or 9, characterized in that: The treatment temperature is 298K-318K, and the treatment time is 6h-12h; preferably, the treatment temperature is 303K-318K, and the treatment time is 3h-12h.